2022
DOI: 10.1038/s41598-022-09177-x
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal microwheel swarms for targeting in three-dimensional networks

Abstract: Microscale bots intended for targeted drug delivery must move through three-dimensional (3D) environments that include bifurcations, inclined surfaces, and curvature. In previous studies, we have shown that magnetically actuated colloidal microwheels (µwheels) reversibly assembled from superparamagnetic beads can translate rapidly and be readily directed. Here we show that, at high concentrations, µwheels assemble into swarms that, depending on applied magnetic field actuation patterns, can be designed to tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…The film thickness between the beads and the interface can be calculated by balancing the weight of the beads with the electrostatic repulsive forces between the beads and interface. 10,28 For the air/water interface, this film thickness should vary with μbot size and is estimated to be ∼50−60 nm. Supporting this, we observe no evidence of capillary interactions under normal experimental conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The film thickness between the beads and the interface can be calculated by balancing the weight of the beads with the electrostatic repulsive forces between the beads and interface. 10,28 For the air/water interface, this film thickness should vary with μbot size and is estimated to be ∼50−60 nm. Supporting this, we observe no evidence of capillary interactions under normal experimental conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Here, particles still settle due to gravity but, in the presence of surfactant and following the work of Martinez-Pedrero et al , in their studies of magnetic rollers at the air/water interface, remain suspended in the liquid phase. The film thickness between the beads and the interface can be calculated by balancing the weight of the beads with the electrostatic repulsive forces between the beads and interface. , For the air/water interface, this film thickness should vary with μbot size and is estimated to be ∼50–60 nm. Supporting this, we observe no evidence of capillary interactions under normal experimental conditions. , Without added surfactant, however, beads do become pinned at the interface. Once bound, surface tension forces dominate any magnetic forces preventing paddlebots from reorienting out of the interfacial plane and translating.…”
Section: Resultsmentioning
confidence: 99%
“…As one would expect, rolling downhill increases translational velocities while travel up steep slopes slows μ$\umu$wheel movement; however, we have recently shown that, with appropriate field application, both individual and swarms of μ$\umu$wheels can continue to move up inclines as high as 80˚. [ 39 ] We note here also that viscosity can play a significant role; with Vω$V\sim \omega $ for constant size μ$\umu$wheels, we expect V1/η$V\sim 1/\eta $ and a slowing down as viscosity increases. For travel from the bronchiole to the alveoli over 10′s of cm, we expect μ$\umu$wheels to travel along the lower‐viscosity sprayed fluid atop the higher‐viscosity lung fluids already present while transport distances through the thicker mucus layer are significantly shorter and up to a few hundred µm.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we have shown that magnetic microwheels (μ-wheels), disk-like assemblies of superparamagnetic polystyrene microparticles, can translate at speeds of hundreds of μm/s along surfaces when driven by 1–10 mT rotating magnetic fields, 27 29 deliver therapeutic proteins, 30 , 31 and behave like swarms through complex vessels. 32 To build upon that work, we sought to create magnetically manipulated hydrogel-based milliwheels (m-wheels) designed for translation along mucosal tissues and controlled release of therapeutic proteins with swarm-like behavior. These m-wheels are synthesized by embedding paramagnetic iron oxide particles in chitosan microparticles with sizes defined by sieve-based fabrication.…”
Section: Introductionmentioning
confidence: 99%